Analisis Hukum Dispensasi Perkawinan Anak di Bawah Umur (Studi Pengadilan Agama Medan) - Hamid, Abdul; Ahmad, Akiruddin; Sahbudi, Sahbudi (Jurnal Ilmiah Penegakan Hukum, 2025)
Legal Analysis of Marriage Dispensation for Minors (Medan Religious Court Study). This study aims to determine the legal provisions regarding Marriage Dispensation for Minors based on PERMA Number 5 of 2019 and other related regulations; to determine the considerations of Medan Religious Court judges regarding the granting of Marriage Dispensation for those who are granted and those who are rejected; and to determine the legal protection for minors who are applying for marriage dispensation. The research method employed in this study is qualitative, utilizing a normative legal approach. The research approaches used are the statute approach and the case approach. The results of the study indicate that the implementation of Perma Number 5 of 2019 prioritizes the best interests of children, specifically in relation to health risks to women's reproductive health. The decision to grant marriage dispensation must include a comprehensive evaluation of the child's physical health and educational readiness, as well as the long-term impacts that may arise from early marriage; and legal protection for minors who apply for marriage dispensation as reviewed from Law Number 16 of 2019 concerning marriage, does not reflect legal protection for the community, due to the low age limit stipulated in the Law.